Respuesta :

Answer:

D. 3

Step-by-step explanation:

2 (x + 10) = x + 23

2x + 20 = x +23

-x            -x

x + 20 = 23

   -20    -20

x = 3

Hey there!

  • [tex]\bold{2(x+10)=x+23}[/tex]
  • Firstly, you have to distribute
  • [tex]\bold{2(x+10)}[/tex]
  • [tex]\bold{2(x)=2x}[/tex]
  • [tex]\bold{2(10)=20}[/tex]
  • [tex]\bold{2x+20=x+23}[/tex]
  • Now, let's do the opposite of [tex]\bold{addition}[/tex] which is [tex]\bold{subtraction}[/tex], so we have to SUBTRACT by [tex]\bold{20}[/tex] on each of your sides
  • [tex]\bold{2x+20-20=x+23-20}[/tex]
  • [tex]\bold{Cancel:20-20}[/tex]
  • [tex]\bold{Keep:2x=x+3}[/tex]
  • [tex]\bold{Simplify}[/tex] it[tex]\uparrow[/tex]
  • SUBTRACT by the [tex]\bold{x}[/tex] value on each of your sides
  • [tex]\bold{2x-x=x+3-x}[/tex]
  • [tex]\bold{Simplify}[/tex] that as well [tex]\uparrow[/tex]
  • [tex]\boxed{\boxed{\bold{Answer:x=3}}}\checkmark[/tex]

Good luck on your assignment and enjoy your day!

~[tex]\bold{LoveYourselfFirst:)}[/tex]

ACCESS MORE